Graduate and undergraduate studies: neighbors without affinity? - MENANDRO, Paulo Rogério Meira (2015)
This article presents two sets of information of historical interest for Psychology: regarding the context in which the profession of psychologist was regulated, and the graduate level formation. These sets of information are used to discuss the difficulty in promoting de facto articulation between undergraduate and graduate level programs. This is an especially curious difficulty, as, since the initial phase of the organization of the Brazilian Graduate Program, the need to consider its integration with the undergraduate formation has always been highlighted. Nevertheless, some difficulties still persist with respect to this integration. Some proposals of activities that could provide articulation between the different levels of formation are presented for debate, both in the sphere of teaching and supervision, as well as in the context of research, with related activities that can serve the same purpose also being mentioned.